2017
DOI: 10.1002/anie.201702313
|View full text |Cite
|
Sign up to set email alerts
|

Binary Encoding of Random Peptide Sequences for Selective and Differential Antimicrobial Mechanisms

Abstract: Binary encoding of peptide sequences into differential antimicrobial mechanisms is reported. Such sequences are random in composition, but controllable in chain length, are assembled from the same two amino acids, but differ in the stereochemistry of one. Regardless of chirality, the sequences lyse bacteria including the "superbugs" methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococci (VRE). Sequences with the same chirality, so-called homochiral sequences, assemble into anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 39 publications
1
45
1
Order By: Relevance
“…Our previous studies have demonstrated that, when composed of natural L ‐amino acids, the random peptide mixtures assemble into pore‐like structures in the membrane. In contrast, heterochiral analogs, composed of one L ‐amino acid and one D ‐amino acid, attack the membrane without oligomerization to pores . The differences in membrane lipid composition might explain the variable susceptibility to antimicrobial peptides.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Our previous studies have demonstrated that, when composed of natural L ‐amino acids, the random peptide mixtures assemble into pore‐like structures in the membrane. In contrast, heterochiral analogs, composed of one L ‐amino acid and one D ‐amino acid, attack the membrane without oligomerization to pores . The differences in membrane lipid composition might explain the variable susceptibility to antimicrobial peptides.…”
Section: Resultssupporting
confidence: 59%
“…This process produces 2 n (where n is the peptide chain length) sequences of random peptides with a defined composition and controlled chain length. Our previous studies have demonstrated that 20 amino acids represents the optimal length and that a 1:1 molar ratio produced random peptide mixtures with strong antimicrobial activity and antibiofilm properties. By synthesizing 20‐mers, we generate approximately one million (2 20 ) peptides that have controlled composition, chain length, and stereochemistry, but are totally random in term of sequence.…”
Section: Introductionmentioning
confidence: 99%
“…The live-dead assays provide accurate estimations of antimicrobial action at the level of individual cells. However, the tests are devoid of contributions from other factors such as the phenotypic tolerance of bacteria to antibiotics and inoculum effects 32 . Optical density measurements performed for the bulk of bacterial culture over much longer periods of time give more generic estimations of biological activity.…”
Section: Resultsmentioning
confidence: 99%
“…Longer HDPs can incorporate sub-domains to anchor to membranes, adjust to membrane curvature, thin and micellise the membranes or intercalate in the bilayer at an angle bending the bilayer pores into toroidal structures 29 31 . Synthetic sequences composed of only cationic and hydrophobic residues can be hemolytic and fold in solution via interfacing hydrophobic faces 32 . This is also common for naturally occurring HDPs including human cathelicidins whose activity varies due to their tendency to form helical bundles that propagate into filament-like structures 33 or highly hemolytic melittins that self-regulate pore formation 34 .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] These designed analogs are expected to overcome the typical limitations of peptides in terms of stability. Most reports to date exploited classical linear or cyclic chain topologies while introducing alternative building blocks such as D-enantiomeric [9][10][11][12] and βamino acids, 13 peptoids, [14][15][16][17][18][19][20] nylon, 21,22 or urea linked diamines. 23,24 In our approach by contrast, we explore unusual multibranched topologies of the peptide chain, such as peptide dendrimers and bicyclic peptides, while keeping building blocks constant.…”
Section: Introductionmentioning
confidence: 99%